New Rules, New Roles: Technology Standards and Teacher Education - Becky Pasco; Phyllis G. Adcock (Educational Considerations, 2007)
The digital age is infiltrating colleges of education around the country, but while some faculty are jumping on the bandwagon and working hard to improve their own technological literacy and that of their students, other faculty are resistant, afraid that technology may “dehumanize” education.
Keywords: expectations; colleges; education; teacher; standards; new rules; new roles; faculty; technology